Model Evaluation of Continuous Data Pharmacometric Models: Metrics and Graphics. (10th February 2017) - Nguyen, T. H. T.; Mouksassi, M‐S; Holford, N; Al‐Huniti, N; Freedman, I; Hooker, A. C.; John, J.; Karlsson, M. O.; Mould, D. R.; Pérez Ruixo, J. J.; Plan, E. L.; Savic, R; et al.
Abstract : This article represents the first in a series of tutorials on model evaluation in nonlinear mixed effect models (NLMEMs), from the International Society of Pharmacometrics (ISoP) Model Evaluation Group. Numerous tools are available for evaluation of NLMEM, with a particular emphasis on visual assessment. This first basic tutorial focuses on presenting graphical evaluation tools of NLMEM for continuous data. It illustrates graphs for correct or misspecified models, discusses their pros and cons, and recalls the definition of metrics used.